A Framework for Improving Patient Satisfaction by Reducing the Length of Stay in The Operation Suite Using the Combined DEMATEL-ANP Model - Mousavi, Seyedeh Raahil; Sepehri, Mehdi; Najafi, Seyed Esmaeil (Decision Making: Applications in Management and Engineering, 2024)
Operating room (OR) planning has gradually become an important element of Hospital administration in recent years. The OR performance plays a significant role in enhancing the quality of the care provided to the patients and reducing patients' length of stay (LOS), which is the function of the OR performance, decreasing costs. Following a survey of the existing research and conducted interviews with clinical and non-clinical OR staff, there are several factors influencing patients’ length of stay (LOS) in the OR and, consequently, the costs of the OR. In this work, first, we implemented the DEMATEL to define the relationship between OR factors, next, employed ANP to identify the most influential factors on the LOS in the OR. The results show the most influential factors are operative time, operative setup, patient waiting time, anesthesia, and patient preparation. Running two rooms concurrently and minimizing turnover time (TOT) reduce patients' LOS by 10% and 5.6%, respectively, and improve the patients' and clinical personnel's satisfaction. Reducing the LOS not only leads to reduced OR costs but also helps increase the number of operations and, thereby, hospitals' revenue.